PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN (Studi Pada Penumpang Kereta Api Kelas Argo Jurusan Semarang-Jakarta PT. KAI DAOP IV Semarang) - Reinhard, Reinhard; Hermani, Agus; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2013)
Along the times, the mobilization of people in the world get increased, including Indonesia. The convenient, fast and safe transportation is needed for society to support their mobility. PT. Kereta Api (Persero) is a state-owned facilities and infrastructure that manages the railway transportation in Indonesia. To win the competition of transportation business, an entrepreneur services or service company must give priority to customers satisfaction. The product launched names argo muria and argo sindoro is an effort to increase customer satisfaction.The problem of this research is the number of passengers declined from the year 2008 to 2012. The purpose of this study was to determine the influence of service quality and price on customer satisfaction argo class train argo track Semarang - Jakarta.The type of this research is an explanatory research. The number of samples in this study were 96 respondents taking using purposive sampling. Data was collected through interviews and literature study. Data analysis using linear regression test with SPSS 16.0.The results showed that the quality of service has an influence on customer satisfaction with a correlation coefficient of 0.835 and a coefficient of determination of 69.7%, the price has influence on customer satisfaction with a correlation coefficient of 0.719 and a coefficient of determination of 51.7%, service quality and price simultaneously have influence on customer satisfaction with a correlation coefficient of 0,841 and a coefficient determination of 70,8%.Suggestions for this company is they needs to improve the quality of service and the price should be reviewed considering other modes of transport is cheaper and efficient.